O impacto da adoção das IFRS nas demonstrações contábeis: uma pesquisa do segmento de transportes aéreos das empresas listadas na Bovespa - Santos, Luciano Aparecido dos (2012)
As a reflex of the changes happened in the last decades in the process of globalization of the economy and of the development of the international markets, it was necessary a change in the process of generation of the accounting information in which accounting has been pressed by the demands of new markets, its potential investors and analysts to supply financial statements in an efficient and effective way for the best interpretation and decision in this market in high performance. As we insert the accounting in this globalization context, the accounting information becomes more and more relevant and of great importance in the decision process. Faced with the economic globalization of the markets, it is necessary the adoption of rules and accounting patterns globally used and accepted, allowing a comparative of the accounting information for the decisorial process. The IASB (International Accounting Standard Board) was responsible for the elaboration of international rules already in convergence process in more than 100 countries all over the world. In Brazil, with the publication of the Law number 11.638/07, being in force from January 1st, 2008, and later with the changes coming from the Law number 11.941/09, there was an important step in the process of convergence of their rules with the international patterns through the creation of the Committee of Accounting Pronouncements (CPC), responsible organ for the emission of accounting pronouncements in consonance with the International Financial Reporting Standards (IFRS). This study aims to identify the materiality of the impacts of the adoption of the International Financial Reporting Standards (IFRS) in financial statements and in companies performance, presenting the significant differences in accounts of Balance Sheet and of Incoming Statement, aiming to answer to the central question: Has the adoption of International Financial Reporting Standards (IFRS) generated impact on Equity and Profit and Loss Statement of the open capital entities listed in BOVESPA, Air Transport segment? To such purpose, it was chosen the methodology of research and of exploratory nature with descriptive studies, which provides to the researcher a larger inclusion of the occurred facts in relation to a direct research. The comparative analysis of the financial statements of the companies object of this study demonstrates that the financial statements elaborated in agreement with the International Financial Reporting Standards (IFRS) present a larger level of disclosure when compared with the old adopted pattern BR GAAP (Generally Accepted Accounting Principles). The obtained conclusion is that the process of adoption of the International Financial Reporting Standards (IFRS) has generated impacts in the Equity and Profit and Loss Statement and in several processes and controls of the companies object of this study